Pengembangan Sains dan Perempuan Potret Semangat Ajaran Islam - Suryadi, Suryadi (Musawa Jurnal Studi Gender dan Islam, 2007)
In the current phase of modernity, according to observation, the condition of women is still positioned as a subordinate being and is only for domestic "use". This vulnerable and dangerous position has made women into the object of releasing violence in many aspects of life not excluding the aspect of industrializing science and technology. This condition is an empiric-visual shape which indicates that patriarchal culture still reigns in life and has infected its way to education. If discussed and understood, this condition is very reflective of true Islamic teachings. By looking at such conditions, this text tries to re,discuss the spirit of Islamic teaching in the context of developing science that is based on equality.